Exploring Social Motivation for Selecting English Language Teaching as a Profession (Vox Batauli, 2025)
Social motivation plays a significant role in selecting the English language teaching as a profession in Nepal. The study aimed to explore social motivation and social factors that shape individuals to choose the English language teaching profession. It examined the motivation provided through social norms, values, expectations, and aspirations to influence English language teachers’ profession choices and identities. The study employed a narrative inquiry method that used the in-depth interview method to collect data. The study participants were three English language teachers from secondary-level schools of a municipality of Rupandehi. They were purposively selected from three secondary schools in the selected municipality. We used the thematic analysis method in the analysis of the data. This study found that the decision to select teaching English as a profession in Nepal is significantly influenced by social motivation rather than purely personal or economic interests. Additionally, the study revealed that English language teaching is a platform for social identity, mobility, where teachers and students get access to networks of local, national and global participation and progress. The implication of the study is to respect the social and civil roles of English language teachers for community engagement and social mobility in EFL context of Nepal.